Polycyclic aromatic hydrocarbons in foods from the first regional total diet study in Sub-Saharan Africa: contamination profile and occurrence data. (September 2019) - Ingenbleek, Luc; Veyrand, Bruno; Adegboye, Abimbola; Hossou, Sètondji Epiphane; Koné, Abdoulaye Zié; Oyedele, Awoyinka Dada; Kisito, Chabi Sika K.J.; Dembélé, Yara Koreissi; Eyangoh, Sara; Verger, Philippe; Leblanc, Jean-Charles; Durand, Sophie; et al.
Abstract: As part of the first multi-centre Sub-Saharan Africa Total Diet Study, 660 typical foods from Benin, Cameroon, Mali, and Nigeria were purchased, prepared according to local consumption habits, and pooled into 55 composite samples. These core foods were tested for 15 + 1 EU priority polycyclic aromatic hydrocarbons, which were quantified by isotope dilution and gas chromatography tandem mass spectrometry. The sum of benzo[a]pyrene, benzo[a]anthracene, benzo[b]fluoranthene, and chrysene (PAH4) represented 77% of the 13 genotoxic and carcinogenic PAHs. The highest PAH4 concentration was quantified in sea and fresh water smoked fish (mean: 179.7 μg/kg; max: 560.4 μg/kg) and the PAH4 in all smoked fish composite samples exceeded the EU maximum limit of 12 μg/kg. Further, PAH4 in edible oils (including palm oil and peanut oil) exceeded the EU maximum limit of 10 μg/kg in 50% of the cases (mean 12.0 μg/kg; max: 60.6 μg/kg). These data can be used for assessing the contribution of core foods to dietary exposure and for risk characterization. Graphical abstract: Image 1 Highlights: Representative foods were prepared as consumed and were pooled before analysis. Smoked fish composite samples exceeded the EU limit for PAH4 in 100% of cases. Edible oils exceeded EU limits for PAH4 in 50% of cases.